On a structure satisfying FK−(−)K+1F=0 - Lovejoy S. Das (International Journal of Mathematics and Mathematical Sciences)
In this paper we shall obtain certain results on the structure defined by F(K,−(−)K+1) and satisfying FK−(−)K+1F=0, where F is a non null tensor field of the type (1,1) Such a structure on an n-dimensional differentiable manifold Mn has been called F(K,−(−)K+1) structure of rank r, where the rank of F is constant on Mn and is equal to r In this case Mn is called an F(K,−(−)K+1) manifold. The case when K is odd has been considered in this paper